Implementation of analytical hierarchy process and simple additive weighting for major selection - Muhammad Ainur Rony; Suwaebatul aslamiyah; Motika Dian Anggraeni (Institute of Computer Science (IOCS), 2023)
A decision support system is a system that can quickly solve problems that occur in rankings and can find out the highest to lowest values in an election. This study aims to implement the Analytical Hierarchy Process and Simple Additive Weighting methods in analyzing data on criteria and decision alternatives that can be used by prospective students who are still unsure about which major to take in college. The criteria used in this study were suitability with educational background, semester fees, employment, interests and talents and parents' requests. while the alternatives used are all faculties and study programs at Budi Luhur University. The analysis was carried out using the Analytical Hierarchy Process method to determine the weight of the criteria used and the Simple Additive Weight method to find out the ranking of non-uniform assessments to determine the priority of alternative choices. The results of the analysis using the two methods are that the engineering faculty is ranked 1 (one), meaning that the best choice for majors based on the criteria compiled is the engineering faculty with a choice of two majors, namely architecture and electrical engineering.